2019
DOI: 10.1021/acs.energyfuels.9b00008
|View full text |Cite
|
Sign up to set email alerts
|

Pore Structure and Integrity of a Bio-Coke under Simulated Blast Furnace Conditions

Abstract: Coke produced with 7.5 wt % charcoal addition and its base blend coke were subjected to gasification and annealing simulating the conditions within an iron-making blast furnace (BF). The changes in the pore structure of cokes during gasification and annealing were studied using image analysis to understand the effect of charcoal addition on pore structure development and degradation mechanism of coke under blast furnace operating conditions. The addition of charcoal had no significant effect on the coke pore s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…The use of biomass particles in comparison with pellets also has a noticeable effect on the size composition of the resulting biocoke. The size of cokes >25 mm, which is used for BF purposes, decreases with an increase in the percentage of biomass pellets due to increased fracturing and porosity [ 68 ]. Consequently, the amount of biocoke with 25–10 mm and 10 mm for non-BF purposes increases.…”
Section: Resultsmentioning
confidence: 99%
“…The use of biomass particles in comparison with pellets also has a noticeable effect on the size composition of the resulting biocoke. The size of cokes >25 mm, which is used for BF purposes, decreases with an increase in the percentage of biomass pellets due to increased fracturing and porosity [ 68 ]. Consequently, the amount of biocoke with 25–10 mm and 10 mm for non-BF purposes increases.…”
Section: Resultsmentioning
confidence: 99%
“…This increases the number of active carbon sites that can be attacked by CO 2 , which enhances the gasification. Flores et al [52] and Xing et al [53] reported that a higher surface area of bio-coal and a greater number of active sites enhance bio-coke gasification. The combination between active carbon sites and remaining catalytic elements in the bio-coal promotes the gasification of bio-coke due to the formation of intermediate complexes, as claimed by others [54][55][56].…”
Section: Influence Of Modified Bio-coal Addition On Coke Reactivitymentioning
confidence: 99%
“…[7] Several different compositions of biomasses and biochar have been reported in literature. [8][9][10][11][12][13][14] This work compares the composition of the formed BF slag when fossil-based coke is replaced with bio-based coke and pulverized coal is replaced with charcoal. To conduct this comparison, compositions for each of the coke (metallurgical coke and biocoke where 3 wt% of coal blend is replaced with Swedish wood charcoal [15] ), pulverized coal, [16] and charcoal (produced from pine chips, [9] eucalyptus, [12] acacia, [13] red gum, [13] and wheat straw [13] ) were chosen from literature and ash compositions were scaled to 100% focusing on the four main components, as shown in Table 1.…”
Section: Introductionmentioning
confidence: 99%